Subgaleal migration of the distal catheter of a ventriculoperitoneal shunt. - Erol, Fatih Serhat; Akgun, Bekir (My University, 2009)
Proximal migration of the distal end of a ventriculoperitoneal shunt has been observed much more rarely than other numerous shunt-related complications. Subgaleal migration of the peritoneal end is one of the samples. In the preset report we have discussed a case of subgaleal migration of the peritoneal end detected as a result of the examinations performed for shunt dysfunction. There was ventricular dilatation on CT scan of the brain. X-ray examinations confirmed proper ventricular catheter and shunt valve placement but a complete migration of distal (peritoneal) catheter into the subgaleal space. Then the patient's shunt was revised. When our case and the literature were examined, we observed that this complication was frequently encountered during the first postoperative months, in the pediatric ages and in patients with advanced hydrocephalus. Besides, we have detected that the peritoneal catheters had tendency to migration into the subgaleal tissues similar to pre-insertion forms of the preoperatively original packages.
Keywords: Female; Foreign-Body Migration; Humans; Hydrocephalus; Infant; Ventriculoperitoneal Shunt; article; brain ventricle peritoneum shunt; case report; female; foreign body; human; hydrocephalus; infant